"I run inside the buildings": adolescents' perceptions of physical health and nature in family homeless shelters. Issue 2 (3rd July 2019) - Cronley, Courtney; Keaton, Craig; Hopman, David D.; Nelson, Larry P.
ABSTRACT: This article reports results from two focus groups designed to understand perceptions of health and nature among adolescents living in emergency family shelters. Following institutional review board (IRB) approval, the authors conducted one focus group each at two emergency family shelters in a high-density suburb in the southern United States with a total of eight adolescents (ages 13–17; 100% African American; 3 males). The study followed the tenets of interpretive phenomenological analysis (IPA) in question design, data collection, and analysis. Four themes emerged from the data: (1) you are what you eat (2) healthy food is not always an option (3) physical activity makes you healthy, but it's hard in a shelter and (4) nature is an abstract ideal . The adolescents expressed a desire to lead healthy lives but were stymied by the built environment; they described nature in idyllic terms but rarely reported engaging in outdoor leisure activities. Findings offer preliminary evidence supporting the need to provide adolescents in family shelters with enhanced access to outdoor physical activity opportunities and fresh foods. Results also highlight the importance of future research into how the built environment contributes to physical and mental health disparities among adolescents in high poverty situations such as homelessness.